Project communications : a critical factor for project success - Plowman, Connie; DIffendal, Jill (Portfolio and project management collection., 2020)
This book presents a new way to look at communication within projects. It combines real-world examples and practical tips with theory, research, and professional standards that can be applied to any size and type of project. Gain actionable in- sights into identifying your audience, choosing the right tools, managing change, and handling confiict. Expand your professional toolkit with templates, activities, and re- sources. Develop your project communications expertise with reflective questions and recommendations. Make your project communications a critical factor in your project success.